The Urban Response to the Demand for Sporting Facilities: A Study of Ten Ontario Towns/Cities, 1919-1939 - Metcalfe, Alan (Urban History Review / Revue d'histoire urbaine, 1983)
In the 1920s and 1930s the growth of sport in urban centres resulted in a significant expansion of recreation facilities. Symbolically, these new facilities resulted in a further expansion of sporting activities. This study of ten Ontario towns/cities indicates that these facilities were provided and maintained in part through public funds and in part through private and co-operative financing. The means adopted in each case varied according to the size of the community, the attitudes of key individuals and groups, and other local idiosyncrasies.